(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The industrial sector of the important drivers of economic activity sectors due to having the capabilities and the potential to qualify biggest contribution to the economic development of the country, which requires the availability of a higher degree of safety in industrial organizations, and the preservation of the lives of employees and workers in emergency situations, and that all the work is not without its dangers, which produces in a year of uncertainty in the possible events get in the future, therefore, reduce the dangers that could be exposed to industrial organizations and management are at the heart of the strategic direction which works to stimulate thinking about the future and respond to the changes that occur in theexternal environment and internal environment and achieve an effective balance. And industrial organizations face a number of business risks in the exercise of their activities, and that these organizations the capabilities to withstand such risks are low because of the circumstances faced by the country. So through the adoption of the Strategic Approach in business risk management can be less than the proportion of industrial hazards through risk to these activities, diagnose and work to understand their behavior and reduce their impact and avoid them if possible.